Revision of the stiletto fly genus Neodialineura Mann (Diptera: Therevidae): an empirical example of cybertaxonomy - Winterton, Shaun L. (Zootaxa, 2009)
The endemic Australian genus Neodialineura Mann is revised to include 13 species. Three species are previously described: N. nitens (White) and N. saxatilis (White) from southern mainland Australia and Tasmania, and N. striatithorax Mann from eastern Australia. Ten species are described as new, including N. ataxia sp. nov., N. atmis sp. nov., N. bagdad sp. nov, N. bifaria sp. nov., N. litura sp. nov., N. polygramma sp. nov., N. signum sp. nov., N. spinosa sp. nov., N. tessella sp. nov. and N. trichidion sp. nov. This revision serves as an empirical example for modernising the process of documenting global biodiversity by making taxonomic description and key development more efficient by avoiding redundancy in data handling and using digital media. Complete taxonomic descriptions were generated using online specimen and image databases, and a character matrix in Structured Descriptive Data (SDD) format developed in Lucid Builder to simultaneously generate natural language descriptions and an interactive key. Numerous web resources are provided with taxonomic descriptions throughout the document including: a) links to archived images of all species on Morphbank, b) registration of authors, publications, taxon names and other nomenclatural acts in Zoobank, with assignment of Life Science Identifiers (LSIDs) for each, c) links to Genbank accession records for DNA sequences, and d) assignment of LSIDs to specimen records with links to respective records in an online Therevidae specimen database. Colour images of male and female specimens of all Neodialineura species are included, along with a traditional dichotomous key to species.